Educação e arte: entre os perdidos no meio ambiente e os achados na poética das artes visuais - Barbosa, Mariana Garcia (2008)
This study is part of Line Research and Education Arts PPGE / UFSM. The main objective of this study is to make theoretical and practical considerations of Art, Environment and Continued Training of Teachers of Visual Arts, bearing in mind the educational approaches of Arts Education in front of contemporary issues of daily Ambiência the city of Santa Maria. The importance of the issue is whether the search of interrelated Art and Urban Environment, a claim of education with a Post-Critical thinking-Contemporary. Its theme of education to look at the environment, education and implications related to an aesthetic visions to establish between these two poles of analysis, seeking not the aesthetical of life, but the ethical and aesthetic environment for human interconnected with the Visual Arts in daily socio-cultural life of people. They have as reference for analysis, Franz (2003), Duarte (2000), Kincheloe (1997), Buoro (2002), Hernandez (2000). The approach of the research is qualitative, through a Case Study. The instruments for data collection, are up for interviews with focus groups, participant observation, the log field, and the portfolio processofolio. The survey was conducted in the House of Culture, located in the square Saldanha Marinho, in Santa Maria / RS, by going to two schools of the city, one state and another township. As participants of the same, 5 teachers of Visual Arts. This research points to an opening in the field of arts within the school that offers no means to a satisfactory work of teachers of art. It also demonstrates how we can embed the Visual Arts with the environment in the training of teachers.